1989
DOI: 10.1111/j.1440-1681.1989.tb01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Plasma and Pituitary Prolactin Responses to Bromocriptine in New Zealand Genetically Hypertensive and Normotensive Rats

Abstract: 1. The effects on blood pressure (BP), plasma and pituitary prolactin (PRL) of a 13 day intraperitoneal infusion of bromocriptine (BRC) delivered by osmotic minipump were investigated in genetically hypertensive rats (GHR) and their normotensive (NT) controls. 2. In the GHR, the mean BP in the BRC-treated group over the 13 day period of study was significantly lower than in the vehicle-treated group. In the NT rats, the mean BP in the BRC-treated group over the 13 day period was also significantly lower than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…We have previously reported that chronic BRC treatment produced more significant falls in systolic BP in the GH rats than in the NT rats (Tan & Hutchinson 1989b). In this report, the data on saline and water intakes in these rats showed that BRC did not have a significant enhancing or inhibitory effect on saline intake in the GH rats while it significantly decreased saline intake in the NT rats.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…We have previously reported that chronic BRC treatment produced more significant falls in systolic BP in the GH rats than in the NT rats (Tan & Hutchinson 1989b). In this report, the data on saline and water intakes in these rats showed that BRC did not have a significant enhancing or inhibitory effect on saline intake in the GH rats while it significantly decreased saline intake in the NT rats.…”
Section: Discussionmentioning
confidence: 45%
“…These pumps were implanted in the interscapular region of the rats and discharged into the peritoneal cavity by means of PE 50 cannulae. As described previously, the mean amount of BRC delivered by the pumps to each rat in 13 days was 88.5 mg (Tan & Hutchinson 1989b).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, preeclampsia is characterized by increased urinary prolactin and urinary levels of this hormone correlate with the severity of the disease [77]. Finally, New Zealand rats treated with bromocriptine have significantly lower blood pressure compared to vehicle-treated animals, suggesting that prolactin may play a role in the pathogenesis of hypertension in this animal model [78]. …”
Section: Other Hormones Implicated In Sle Pathogenesismentioning
confidence: 99%
“…We have previously shown that chronic treatment of the G H rats and the normotensive (NT) control rats, with the centrally acting dopaminergic agonist, bromocriptine (BRC) (Nagahama et al 1984), produced greater decreases in systolic blood pressure (BP) and plasma and pituitary prolactin (PRL) levels in the G H rats than in the N T rats (Tan & Hutchinson 1989), suggesting a possible role for P R L in the hypertension of the G H rat.…”
mentioning
confidence: 99%